2015
DOI: 10.1371/journal.pone.0138032
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Evaluation of a Novel Size Based Circulating Tumor Cell Isolation System

Abstract: Isolation of circulating tumor cells (CTCs) from peripheral blood has the potential to provide a far easier “liquid biopsy” than tumor tissue biopsies, to monitor tumor cell populations during disease progression and in response to therapies. Many CTC isolation technologies have been developed. We optimized the Parsortix system, an epitope independent, size and compressibility-based platform for CTCs isolation, making it possible to harvest CTCs at the speed and sample volume comparable to standard CellSearch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
189
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(196 citation statements)
references
References 35 publications
3
189
3
1
Order By: Relevance
“…We have previously shown that CD45 À cells with both epithelial and mesenchymal features can be detected in prostate cancer patients using Parsortix (9). Here, we developed a repeated FISH analysis approach following immunofluorescence analysis on the same slide to investigate multiple genomic regions for alterations and, consequently, establish the malignancy of VIM þ /CD45 À cell populations, which were associated with disease burden and poor prognosis and have the potential to serve as an additional marker to traditional epithelial CTCs for clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that CD45 À cells with both epithelial and mesenchymal features can be detected in prostate cancer patients using Parsortix (9). Here, we developed a repeated FISH analysis approach following immunofluorescence analysis on the same slide to investigate multiple genomic regions for alterations and, consequently, establish the malignancy of VIM þ /CD45 À cell populations, which were associated with disease burden and poor prognosis and have the potential to serve as an additional marker to traditional epithelial CTCs for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of CTCs from whole blood using a size-and deformability-based system Parsortix was performed as described previously (9). Sample harvest and the process of immunostaining are detailed in Supplementary Materials and Methods.…”
Section: Ctc Isolation and Enumerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the processing time of 7.5 mL of whole blood is 2 h in contrast to the 4 h reported for the Cell Search (Cell Search, Jansen Diagnostic). It is worth noting that with the second version of Parsortix 10 mL can be processed in 2.5 h. The main drawback of this technique is the difficulty of eliminating all leukocytes owing to size overlap with CTCs (39 ). In addition to the previous devices described above, ClearCell FX (Clearbridge Biomedics) recovers viable cells in small sample volumes and in a short period of time (e.g., 1 mL of blood in 10 min) (Fig.…”
Section: Methods Based On Physical Propertiesmentioning
confidence: 99%
“…This definition has shown to be quite robust in several ring studies that have been conducted [107,108]. A variety of new technologies have been introduced after the introduction of CellSearch, and most compare the results obtained with those from CellSearch [109][110][111]. A difficulty here is that the definitions used to define a CTC are not the same, thus comparing apples with oranges.…”
Section: Additional Reagents For Cell Labelingmentioning
confidence: 99%